Analisis Pemikiran Abdullah Saeed Tentang Riba dan Bungan Bank Dalam Perspektif Ekonomi Islam - Suryani, Mardian; Capriyanti, Orisa; Khairunnisa, Arista (Politeknik Raflesia Press, 2024)
The aim of this research is to find out Abdullah Saeed's thoughts about usury and bank interest and to find out the Islamic economics review of Abdullah Saeed's thoughts about usury and bank interest. The research carried out was library research (library research) with a qualitative descriptive approach. Data used in this research: Primary data is data obtained through a series of activities and main data sources in research and secondary data is data obtained through collecting or managing data in the form of documentation studies (document analysis) in the form of reviewing personal documents, references. references or regulations (literature reports, writings, etc.) that are relevant to the research object. From the research results it was found that: According to Abdullah Saeed usury is the taking of additional funds from basic assets or capital in vanity. Bank interest does not include usury, because it does not involve exploitation of the poor (not unjust). Islamic economics review of Abdullah Saeed's thoughts regarding usury and bank interest. There are differences in views between Abdullah Saeed and Islamic economics regarding bank interest. Where Abdullah Saeed gives the view that bank interest in conventional banks is permissible because it does not contain elements of injustice, whereas in the Islamic economic system the term interest is not recognized because According to Islam, interest is usury which is forbidden, therefore Islamic economics replaces the interest system with profit sharing. Keywords: Usury, Bank Interest, and Islamic Economics.